ANALISIS MINAT BELAJAR SISWA SMP KELAS VIII DI KOTA BANDUNG TERHADAP PEMBELAJARAN MATEMATIKA - Tita Puspita; Indah Retta Fauziah (Journal on Education, 2019)
This study aims to analyze how the learning interests of middle school students in the city of Bandung. The learning method used is the method of surveying and interviewing students. The research technique was carried out by distributing learning interest questionnaires which were analyzed descriptively. The questionnaire consists of 12 items with 4 alternative answers namely "Strongly Agree" (SS), "Agree" (S), "Disagree" (TS), and Strongly Disagree "(STS). The population carried out in this study were junior high school students in one of the private schools in the city of Bandung with a sample of class VIII totaling 38 people. The results showed an indicator of happy feelings of students towards mathematics learning as much as 70%, attention indicators as much as 43%, indicators of attraction as much as 72% and for knowledge indicators as much as 65%. This shows that the indicators of feelings of pleasure and student interest in mathematics learning are quite optimal even though the indicator of knowledge is still classified as having a low percentage and the indicators of attention are very low.